Determination of Fermentability (Final Attenuation) of Wort: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Hagen, W.; Schwarz, H. (BrewingScience, 1999)
Two methods for the determination of the apparent fermentability (attenuation limit) of wort, the regular fermentation as a reference method as well as a more rapid method have been collaboratively tested by members of the Analysis Committee of the European Brewery Convention to obtain repeatability (r₉₅) and reproducibility (R₉₅) values and to form an idea of the equivalence of these two procedures based on the comparison of results obtained from identical samples. In the collaborative trials the 14th EBC Standard Malt and two industrial worts were analyzed. Repeatability (r₉₅) and Reproducibility (R₉₅) values of 0.5% and 2.9% respectively at a mean level of 83.9% were obtained for laboratory wort from malt using the reference fermentation method. Using the rapid fermentation method the values were 0.9% and 2.4 % respectively at the mean level of 82.8%. The precision values for industrial wort using the reference fermentation method were r₉₅ = 0.4% and R₉₅ = 2.4% for mean levels of 81.3 and 82.4%, using the rapid method 0.3% and 3.5% were obtained respectively for mean levels of 80.5 and 81.7%. The reference fermentation is more precise in terms of reproducibility and yields higher results. The rapid method is recommended for guideline purposes only.